Vimentin deficiency in macrophages induces increased oxidative stress and vascular inflammation but attenuates atherosclerosis in mice. Issue 1 (December 2018) - Håversen, Liliana; Sundelin, Jeanna; Mardinoglu, Adil; Rutberg, Mikael; Ståhlman, Marcus; Wilhelmsson, Ulrika; Hultén, Lillemor; Pekny, Milos; Fogelstrand, Per; Bentzon, Jacob; Levin, Malin; Borén, Jan
Abstract The aim was to clarify the role of vimentin, an intermediate filament protein abundantly expressed in activated macrophages and foam cells, in macrophages during atherogenesis. Global gene expression, lipid uptake, ROS, and inflammation were analyzed in bone-marrow derived macrophages from vimentin-deficient (Vim −/− ) and wild-type (Vim +/+ ) mice. Atherosclerosis was induced inLdlr −/− mice transplanted withVim −/− andVim +/+ bone marrow, and inVim −/− andVim +/+ mice injected with a PCSK9 gain-of-function virus. The mice were fed an atherogenic diet for 12–15 weeks. We observed impaired uptake of native LDL but increased uptake of oxLDL inVim −/− macrophages. FACS analysis revealed increased surface expression of the scavenger receptor CD36 onVim −/− macrophages.Vim −/− macrophages also displayed increased markers of oxidative stress, activity of the transcription factor NF-κB, secretion of proinflammatory cytokines and GLUT1-mediated glucose uptake.Vim −/− mice displayed decreased atherogenesis despite increased vascular inflammation and increased CD36 expression on macrophages in two mouse models of atherosclerosis. We demonstrate that vimentin has a strong suppressive effect on oxidative stress and thatVim −/− mice display increased vascular inflammation with increased CD36 expression on macrophages despite decreased subendothelial lipid accumulation. Thus, vimentin has a key role in regulating inflammation in macrophages during atherogenesis.